Production and yield response factor of sunflower under different irrigation depths - Benito M. de Azevedo; Denise V. Vasconcelos; Guilherme V. do Bomfim; Thales V. de A. Viana; Joaquim R. do Nascimento Neto; Kárcia M. A. S. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Local information about irrigation depths for sunflower can be used in the design of projects and irrigation management to increase crop yield and to reduce costs. This study aimed to evaluate the effects of irrigation depths on sunflower and calculate its yield response factor. The experiment was conducted in Fortaleza-CE, Brazil, in a randomized block design, with six treatments, four replicates and ten evaluated plants per plot. The treatments were applied in the phenological stages II, III and IV with irrigation depths equivalent to 25, 50, 75, 100, 125 and 150% of crop evapotranspiration. The yield response factor was calculated according to FAO Bulletin nº 33. The water supply, equivalent to 79.7 and 91.1% of crop evapotranspiration, increased capitulum mass (43.8 g) and commercial yield of seeds (3,360.2 kg ha-1). Additionally, the yield response factor indicated that sunflower is tolerant to daily irrigation under controlled water deficit.